Toponyms in the poetic language of V. Gerasymjuk: the functional and semantic aspects - Кальченко, Тетяна Юріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The aim of the paper is to analyze the functionality and semantics of toponyms which are characteristic for the V. Gerasymjuk’s poetic language. His lyrics are noted by such key lexical tokens as Ukraine, Kosmach, Goverla as well as appeal to the events of national history and culture; and the concrete verbal reflection of it is different names – oronyms, hydronyms, urbanonyms, oikonyms. The analysis of toponyms is the attempt to determine their functional possibilities as the way of enrichment of the image system of V. Gerasymjuk’s texts.